Implementation of The Independent Learning Curriculum at SMK Negeri 1 Lahewa in The 2022/2023 Academic Year - Inka Kristina Waruwu; Adrianus Bawamenewi; Berkat Persada Lase (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine how the implementation of the independent learning curriculum is, to find out the obstacles faced in implementing the independent learning curriculum and to find out the efforts made in overcoming the obstacles to implementing the independent learning curriculum at SMK Negeri 1 Lahewa in the 2022/2023 academic year. This research uses a qualitative method with a descriptive approach. The purpose of using a descriptive approach is to find meaning starting from facts by making observations recording all facts in a holistic scientific manner with the problems observed. The research instrument is the researcher himself, using a mobile phone as a tool to record all conversations, pictures as real evidence, and a notebook that serves to record conversations with informants. The data collection techniques used were interviews, observation, and documentation. The results of the research and discussion concluded that: First, the implementation of the independent learning curriculum has been implemented but not fully implemented. Of the three categories of independent curriculum implementation, SMK Negeri 1 Lahewa uses the independent learning category option, which means that schools are given the authority to use the 2013 curriculum structure but apply several principles of the independent learning curriculum in the learning process and assessment. Second, the obstacles faced in implementing the independent learning curriculum at SMK Negeri 1 Lahewa are that teachers do not have experience in accordance with this independent learning curriculum. Then there are difficulties in obtaining material references, and including inadequate facilities and infrastructure and internet facilities. Third, the efforts made to overcome the obstacles to the independent learning curriculum are preparing teachers by participating in online-based socialisation to have experience in implementing the independent curriculum, then utilising social media to obtain material references according to the independent curriculum such as modules, books provided by the government and the implementation of facilities and infrastructure and facilities that support the education process by collaborating with the government.